Evaluating the Urban Heat Effects of High Rise Non-Green Buildings: A Case Study in Kota Bharu, Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
This study provides an overview of the urban heat effect of the high rise non-green building in the urban area located in Kota Bharu, Kelantan by collecting and analyzing related data using sky view factor (SVF).The SVF is one of the essential aspects related to pollution, temperature variations, heat island and several other environmental specifications. A common method through fish-eye photographs were taken at ground level with a digital camera together with a detachable 180’ fish-eye lens. The result highlighted the SVF value at six high rise non-green buildings was in a range between 0.24 and 0.67. The highest temperature recorded was 42°C on rooftop of Kelantan Trade Center building whilst the lowest was 30°C on rooftop of Ibu Pejabat Polis Kontinjen Kelantan. The surrounding and building materials were found to have a persistent influence on the formation of urban heat.
Keywords: SVF value; non-green building; urban heat